Understanding Social Media Competence in Higher Education: Development and Validation of an Instrument. (January 2020) - Zhu, Sha; Hao Yang, Harrison; Xu, Shun; MacLeod, Jason
The rapid integration of social media into personal, professional, and educational settings has catalyzed the need to assess social media competence. This study provides the rationale for developing an instrument to conduct such an assessment, and the research illustrates evidence of validity and reliability in assessing social media competence in the field of higher education. The instrument includes 28 items and 4 dimensions: technical usability, content interpretation, content generation, and anticipatory reflection. Data were collected from a sample of 622 college students. Exploratory and confirmatory factor analyses were conducted, and this study finds that the instrument shows no signs of deficiency in its validity or reliability when measuring social media competence. Accordingly, the instrument could be used to evaluate and improve levels of social media competence in higher education.